Abordagem para monitoramento tecnológico e investigação de potencial de mercado em um centro de tecnologia em nanomateriais - Marina Prass Santos (2021)
Trend and technological prospecting studies have been used as a tool to inform strategic decisions in organizations for decades. Among the consolidated methods, Roadmapping stands out for its flexibility and graphic appeal, while patent analysis is a useful technique for extracting information from large amounts of patent data. Inspired by Roadmapping and patent analysis, this work proposes a procedure to technological and market monitoring for a technology center (CTNano / UFMG), based on studies of patent and market documents. The information obtained in these studies is combined in a map that presents possible paths for the Center to act at a strategic level, aiming at disseminating the technology to society and generating value for the organization. A pilot test of this procedure is carried out with a technology of nanostructured polymeric filaments for fused deposition modeling (FDM) printers. In the designed map, two potential areas of activity for CTNano are identified: (i) an attempt to license the patent already deposited with manufacturers of materials for FDM printers that stood out in the studies and (ii) prospection of projects involving end customers interested in the use of materials for additive manufacturing in industrial production contexts, potentially taking advantage of the market position achieved with the previous licensing to propel this initiative. At the end, the text brings implications of the procedure for the management of CTNano and for the practice of future analysis for technologies in the context of new materials.